The impact of social media usage on purchasing decisions (Entrepreneurship Journal for Finance and Business, 2025)
Social media are internet-based digital spaces that aim to facilitate communication and interaction between individuals and different groups. These platforms are characterized by their high interactivity, diverse uses, global reach, and rapid dissemination of information. They can be classified into main types, including:Public platforms: such as Facebook and Twitter, which enable broad communication and the exchange of opinions and information.Content-sharing platforms: such as YouTube and Instagram, which focus on sharing photos, videos, and other content.Professional platforms: such as LinkedIn, which aim to build professional networks and exchange work experiences